STUDY OF SOME BIOCHEMICAL PARAMETERS IN YOUNG MEN AS EFFECTED BY RAMADAN FASTING - Indra, M. Rasjad; Satuman, Satuman; Widodo, Edwin; E.H, Tinny; S.W, Endang; Sudiarto, Sudiarto; Soemardini, Soemardini (Lembaga Penelitian Universitas YARSI, 2007)
The effect of Ramadan fasting on some blood parameters i.e. serum glucose, urea, uric acid, lipids and proteins, were investigated on young men in Ar Rohmah Islamic dormitory. Nineteen normal and healthy students aging between 12-25 years, residing in the Islamic dormitory, voluntarily to participated in the study. Blood samples were obtained from the volunteers on the 1st and 26th day of Ramadan and analyzed for the aforementioned biochemical parameters. A non-significant effect of Ramadan fasting was observed on most of the parameters studied. However, serum urea, triglycerides, total cholesterol and LDL-cholesterol were reduced significantly (p 0.05) but remained within the physiological limits. Decrease in blood urea has been attributed to the effect of at least protein and triglycerides intake to increase lipolytic effect. The reduction in serum cholesterol and LDL is a beneficial effect of Ramadan fasting. The results of the study indicated thatRamadan fasting is quite safe for normal healthy adults.